2006
DOI: 10.1111/j.1532-849x.2006.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication Between the Dental Laboratory Technician and Dentist: Work Authorization for Fixed Partial Dentures

Abstract: Information obtained from the responding laboratories included effectiveness of work authorization forms. There were some similar trends indicated by the large percentage of dental laboratories agreeing on lack of communication by the dentists as reflected by the work authorization forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 8 publications
3
44
0
1
Order By: Relevance
“…This might reveal inadequate written instruction and communication between clinician and laboratory technicians. Which might be due to the fact that the dentist depends on the dental technician to construct the prostheses in specific manner and design, or the dentist interested in writing certain information in the work instruction form over other information, Also it could be due to weak undergraduate training in writing laboratory instructions [1]. Notwithstanding this, the results of this study were comparable, if not slightly better than that observed in other studies [4,28,5,[14][15][16]10,21,12].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…This might reveal inadequate written instruction and communication between clinician and laboratory technicians. Which might be due to the fact that the dentist depends on the dental technician to construct the prostheses in specific manner and design, or the dentist interested in writing certain information in the work instruction form over other information, Also it could be due to weak undergraduate training in writing laboratory instructions [1]. Notwithstanding this, the results of this study were comparable, if not slightly better than that observed in other studies [4,28,5,[14][15][16]10,21,12].…”
Section: Discussionsupporting
confidence: 53%
“…Although, in 96% of the fixed restoration, the shade was indicated, 72% provide a diagram for staining and 73% were indicated the type of porcelain glaze. Using a diagram of a tooth for multiple shades is very helpful to the dental technician, especially in the fabrication of crowns in the anterior region, and indicating the type of porcelain glaze such as auto glazing, over glazing, or polishing [23,1]. Unlike other studies [28,15,16,21] which showed that the majority of the removable partial denture (RPD) cases were designed by the dental technician, this study showed that 95% of the removable partial denture (RPD) cases were designed by the dental practitioners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Afsharzand et al 17 Please complete the second part of this questionnaire by ticking the appropriate box on the scale, with 0 equating to poor (worse) and 5 equating to very good (better)…”
Section: Introductionmentioning
confidence: 99%